Factors influencing women’s entry into entrepreneurship in Malaysia - Iklima Husna Abdul Rahim; Dzulkifli Mukhtar; Siti Salwani Abdullah; Anis Amira Ab Rahman (Global AcademicExcellence (M) Sdn Bhd, 2025)
Women entrepreneurs are individuals who initiate, organize, and operate businesses while navigating various economic, social, and cultural challenges. Globally, their role in driving innovation, creating employment, and contributing to economic growth has gained increasing recognition. In many developing and emerging economies, including Malaysia, women entrepreneurs are becoming key players in transforming traditional gender roles and empowering communities. Despite facing barriers such as limited access to capital, societal expectations, and work-life balance issues, many women continue to break through these challenges with resilience, creativity, and determination. Their entrepreneurial journeys are often influenced by a by a complex interplay of internal and external factors. Encouraging women’s participation in entrepreneurship not only enhances gender equality but also strengthens national development. Therefore, this study aims to identify the factors that drive women’s involvement in entrepreneurship in Malaysia. The findings reveal that experience, financial status, business succession, contribution to the family, and domestic responsibilities are among the main enablers drive women to venture into entrepreneurship. The implications of this study are important for shaping inclusive and sustainable economic development strategies.